PARTISIPASI POLITIK MASYARAKAT DALAM PEMILIHAN KEPALA DESA DI DESA BERANCAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Runi Yulistia; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This thesis is proposed to qualify for a Bachelor of Sociology degree. With the title "Political Participation Society In Head Man Election In Village Berancah District Bantan Bengkalis District". The problem discussed in this thesis is the participation of the community in the election of head man in 2017 and the influence of people's political understanding of their participation in the political activities they participate in and in determining a leader. Public participation in choosing a leader is an investment in politics by the community in order to improve or memajukkan again area.This research was conducted in Berancah Village of Bantan District of Bengkalis Regency. In this study used the functional structural theory of Talcot Parson, this theory explains that every individual in society has its own function. And in carrying out these functions people have different goals that will be achieved. Achievement of goals by society can be done in various forms depending on the path chosen by a particular society or individual.The results of the study generally can be said that most of the people participated in the selection of head man in 2017 in Berancah Village. In this case it is said that the society has done its function in the life of the state to participate in choosing a leader. In addition, the community is also involved in several other political activities such as campaigning on head man elections and other elections and participate in other social activities in socializing. The political understanding of the community is very important for the public assessment in choosing a leader or for public policy issued by the government. The higher of political understanding of the society, the more critical the community will be in addressing the political phenomenon that exist in the environment.Keywords: community, political participation